Image adjustments on digital panoramic radiographs using Adobe Photoshop CS3 software - Sérgio Soares Batista; Francine Kühl Panzarella; Orivaldo Tavano; Agenor Montebelo Filho; José Luiz Cintra Junqueira (Revista Sul-Brasileira de Odontologia, 2014)
: Favourable manipulation of images may be the greatest advantage of the digital radiographic compared to the conventional film. The current development of the cost-benefit of intra- and extraoral digital technology, besides the increase of computerized practices has turned the digital image into a superior alternative to conventional radiographs, in several aspects. Objective: To demonstrate image adjustments on digital panoramic radiographs using Adobe Photoshop CS3 (Creative Suite 3) software in order to enhance digital images. Case reports: Digital treatment was conducted in two different cases using two filters available in Adobe Photoshop CS3: Smart Sharpen and Unsharp-Mask. Both filters improve overall image quality. In the second case, after brightness and contrast adjustments, it was possible to have a detailed visualization of radiopaque and radiolucent areas. Conclusion: The application of brightness and contrast adjustments and filters are feasible methods in order to achieve diagnostic precision.